2017
DOI: 10.33549/physiolres.933733
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and Bone Parameters in Pubertal Girls

Abstract: Here we analyzed associations between muscles mass, total bone mineral content (BMC), lumbar spine bone density (BMD L1-L4) and serum or urine hormones in healthy peripubertal girls. Total BMC and areal BMD L1-L4, muscle mass and fat were measured by dual-energy X-ray absorptiometry (DXA). Muscle force (N) was estimated by a dynamometer. Circulating estradiol, follicle-stimulating hormone (FSH), luteinizing hormone (LH), 25-hydroxy vitamin D, parathyroid hormone (PTH), insulin-like growth factor 1 (IGF-1), lep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Likewise, this adipokine improves the collagenolytic properties in cartilage explant cultures through the activation of matrix metalloproteinases and activation of STAT3 transcription and also inhibited osteoclast formation by increasing osteoprotegerin concentrations. These apparently discordant data may be due to their interaction with other factors, since leptin acts together with other hypothalamic factors, IGF-1, and estrogens [ 265 ], whereas a reduction in leptin levels is related to lower bone mineral density [ 266 ].…”
Section: Functionality Of Leptin and Its Involvement In Pathologymentioning
confidence: 99%
“…Likewise, this adipokine improves the collagenolytic properties in cartilage explant cultures through the activation of matrix metalloproteinases and activation of STAT3 transcription and also inhibited osteoclast formation by increasing osteoprotegerin concentrations. These apparently discordant data may be due to their interaction with other factors, since leptin acts together with other hypothalamic factors, IGF-1, and estrogens [ 265 ], whereas a reduction in leptin levels is related to lower bone mineral density [ 266 ].…”
Section: Functionality Of Leptin and Its Involvement In Pathologymentioning
confidence: 99%
“…Previous studies showed that insulin or insulin-like growth factor-1 (IGF-1) had an important role in osteogenesis [ 38 ]. And the receptors of insulin and IGF-1 are widely distributed on the surface of osteogenic cells and displayed high activity in the differentiation of osteoblast [ 39 , 40 ].…”
Section: The Relationship Between Hyperglycemia and Bone Impairmentmentioning
confidence: 99%
“…Additionally, the connection between body composition, especially fat content in the body, and Vitamin D and leptin in young adults is clinically vital because management that modify body weight may affect bone health and therefore the possibility of osteoporosis in later life. Few studies have attempted to investigate the effect of body composition and leptin with vitamin D in adolescence[17,18]. This study was conducted to analyze serum leptin concentrations in samples from adult volunteers and correlate it with body composition parameters, difference in gender, 25-hydroxy vitamin D (25OHD) and lipids.…”
Section: Introductionmentioning
confidence: 99%